A comparative study between conventional insurance and Islamic Takaful in Prudential Assurance Malaysia Berhad Melaka Branch / Nur Ain Aziz - Aziz, Nur Ain (2009)
Today, insurance as seen as a compulsory thing to have by individual. An insurance policy does not guaranteed to give 100% investment return if the assured never claims while they live but insurance is guaranteed to pay for the anything happens to assured depends on the terms and conditions as promised and agreed by both parties. The elements like riba, maisir and gharar in the insurance also have made people especially Muslims confuse when they want to have an insurance policy. The objective of the study is to identify the characteristics of conventional insurance (Prudential’s insurance) and Islamic insurance (Prudential BSN takaful). At the same time, the study objective is also to know the differences between both insurance concepts. The study of these ideas is to get better knowledge about the both type of insurance offered by Prudential. This is because, there are a few comparison in the insurance features and operating concepts especially its principles, which the prospect or client didn’t know. As a result, they are confuse and don’t know which is better for them especially for Muslim people. In order to void the confusion occurs, all people has to know at least, the principles and operating concepts of both insurance before they make decision to buy the insurance policy. To complete this study, the description of Prudential’s products is needed. The methodology use to study the products is by get the information in the brochure and in the website. This study, however, aims at exploring the differences between the both conventional insurance and takaful concept. At last, clients will know the characteristics of the products that differentiate the both of them. It is sincerely hoped that this study may help prospect or client especially Muslim have a better understanding on insurance before the have it.